Using model checking to find serious file system errors - Yang, Junfeng; Twohey, Paul; Engler, Dawson R.; Musuvathi, Madanlal; Musuvathi, Madan (ACM Transactions on Computer Systems, OSDI 04: Sixth Symposium on Operating Systems Design & Implementation, 2004)
Awarded Best Paper! This paper shows how to use model checking to find serious errors in file systems. Model checking is a formal verification technique tuned for finding corner-case errors by comprehensively exploring the state spaces defined by a system. File systems have two dynamics that make them attractive for such an approach. First, their errors are some of the most serious, since they can destroy persistent data and lead to unrecoverable corruption. Second, traditional testing needs an impractical, exponential number of test cases to check that the system will recover if it crashes at any point during execution. Model checking employs a variety of state-reducing techniques that allow it to explore such vast state spaces efficiently. We built a system, FiSC, for model checking file systems. We applied it to three widely-used, heavily-tested file systems: ext3, JFS, and ReiserFS. We found serious bugs in all of them, 32 in total. Most have led to patches within a day of diagnosis. For each file system, FiSC found demonstrable events leading to the unrecoverable destruction of metadata and entire directories, including the file system root directory “/”.